(untitled) (European Journal of Pure and Applied Mathematics, 2024)
This paper introduces a new class of functions called δ(τ_1,τ_2)-continuous functions. Several characterizations of δ(τ_1,τ_2)-continuous functions are investigated. The relationships between δ(τ_1,τ_2)-continuity and the other types of δ(τ_1,τ_2)-continuity are also discussed.